Phylogenetic profiling resolves early emergence of PRC2 and illuminates its functional core - Sharaf, Abdoallah; Vijayanathan, Mallika; Oborník, Miroslav; Mozgová, Iva (Life science alliance, 2022)
Polycomb repressive complex 2 (PRC2) is involved in maintaining transcriptionally silent chromatin states through methylating lysine 27 of histone H3 by the catalytic subunit enhancer of zeste [E(z)]. Here, we report the diversity of PRC2 core subunit proteins in different eukaryotic supergroups with emphasis on the early-diverged lineages and explore the molecular evolution of PRC2 subunits by phylogenetics. For the first time, we identify the putative ortholog of E(z) in Discoba, a lineage hypothetically proximal to the eukaryotic root, strongly supporting emergence of PRC2 before the diversification of eukaryotes. Analyzing 283 species, we robustly detect a common presence of E(z) and ESC, indicating a conserved functional core. Full-length Su(z)12 orthologs were identified in some lineages and species only, indicating, nonexclusively, high divergence of VEFS-Box-containing Su(z)12-like proteins, functional convergence of sequence-unrelated proteins, or Su(z)12 dispensability. Our results trace E(z) evolution within the SET-domain protein family, proposing a substrate specificity shift during E(z) evolution based on SET-domain and H3 histone interaction prediction.
Keywords: Drosophila Proteins; lysin; fylogeneze; proteiny Drosophily; Lysine; Polycomb Repressive Complex 2; Phylogeny; PRC2; histony; Histones